(untitled) (University Heart Journal, 2020)
Antiplatelet therapy is the cornerstone in the treatment of acute coronary syndrome. Aspirin is the most widely used antiplatelet agent followed by P2Y12 inhibitors. Glycoprotein (GP) IIb-IIIa antagonists are also gaining popularity as an antiplatelet agents during peri-PCI period. This review article summarizes the indications, duration of dual antiplatelet therapy (DAPT) in ACS setting. Antiplatelet therapy in special situations like atrial fibrillation and thrombocytopenia are discussed here. Issues like switching between P2Y12 inhibitors and genetic testing of antiplatelet agents are also mentioned in this article University Heart Journal Vol. 17, No. 1, Jan 2021; 66-70